Peran Profil Perpustakaan Dalam Penguatan Program Literasi Sekolah - Rafa Nabila Puteri; Ade Akhmad Saputra; Arwan, Arwan; Duangkamol Aemevat (CV. ITTC INDONESIA, 2025)
School libraries play an important role in supporting learning and promoting a culture of literacy among students. As an information and learning resource centre, the library not only provides a collection of books but also contributes to forming sustainable reading habits. However, for this function to be optimised, the library needs to have a clear and systematic profile. The library profile serves as a comprehensive description of the library's condition, services, infrastructure, and programmes that have been and will be implemented. This study aims to analyse how the library profile can be a reference in strengthening the literacy program at SMA Negeri 1 Palembang. Using a qualitative approach with literature study and participatory mentoring methods, this research involved direct observation, interviews and document analysis related to school literacy policies and library standards. Data analysis techniques used with data triangulation were conducted to ensure the validity of the findings by comparing information from various sources. The results showed that developing a comprehensive library profile not only facilitates library management but also strengthens accreditation, increases student engagement in literacy activities and opens up opportunities for collaboration with various parties. In addition, the findings in this study also show that library profiles can be an instrument in planning and evaluating school literacy programmes. With a systematic and structured library profile document, the library can be more optimal in supporting students' academic achievement and building a sustainable literacy culture in the school environment.